Controle de bicho-mineiro com nematóides entomopatogênicos e uso de imagens para detecção de minas - Mendonça, Thiago Fellipe Nunes de (2021)
The coffee crop is one of the main commodities exported by Brazil, with it being responsible for around 70% of world production. With a revenue of around US$5.6 billion per year, however, its production is greatly affected by pests and diseases, directly interfering with the volume of the product. One of the pests that affect productivity is the Leucoptera coffeella, popularly known as Bicho-Mineiro, that's why this research aims to evaluate the control of the miner by the biological control method with entomopathogenic nematodes and determination of the infestation rate in coffee plantations, carrying out its monitoring by the photogrammetric imaging method compared to conventional sampling.